Proceedings of the International Conference of Health Development. Covid-19 and the Role of Healthcare Workers in the Industria 2020
DOI: 10.2991/ahsr.k.201125.053
|View full text |Cite
|
Sign up to set email alerts
|

Study of Covid-19 Prevention: Diet and Physical Activity During Large-Scale Social Restrictions in West Sumatera

Abstract: Coronavirus Disease or known as COVID-19 is currently a global health problem. COVID-19 is a new disease caused by a virus called Sars-Cov-2. The first case in West Sumatera Province was reported on March 18, 2020. As of May 2, 2020, total of 182 positive cases of COVID-19 have been confirmed in West Sumatera Province. The Government of the Republic of Indonesia has issued Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions (PSBB) in the framework of the Acceleration of Handling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[ 34 ] That study also found that even countries which had relatively low COVID-19 infection rates and have therefore do not imposed lockdowns, such as South Korea, Taiwan, and Japan, also exhibited decreases in overall step counts. [ 34 ] That study, though, did not include data from Indonesia and other southeast Asian regions; thus our study as well as other studies in Indonesia[ 39 40 ] in part contributed to confirm the decrease of physical activity levels in this region during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[ 34 ] That study also found that even countries which had relatively low COVID-19 infection rates and have therefore do not imposed lockdowns, such as South Korea, Taiwan, and Japan, also exhibited decreases in overall step counts. [ 34 ] That study, though, did not include data from Indonesia and other southeast Asian regions; thus our study as well as other studies in Indonesia[ 39 40 ] in part contributed to confirm the decrease of physical activity levels in this region during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 53%
“…While few studies have assessed physical activity levels in Indonesia during the COVID-19 pandemic,[ 39 40 ] to our knowledge, this study is the first longitudinal study comparing the physical activity levels before and during the COVID-19 pandemic among previously active young adults in Indonesia. We found that physical activity levels decreased significantly during the pandemic.…”
Section: Discussionmentioning
confidence: 99%